PRAKTIK JUAL BELI KIOS BERJANGKA PRESPEKTIF FIQH MUAMALAH (Studi Kasus di Balai Akaik Saruaso) - Intan Nafri Yulita; Elsy Renie (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This study examines the practice of buying and selling futures at Balai Akaik Saruaso. The problem is the fiqh muamalah review of the practice of buying and selling futures at the Saruaso Akaik Hall. Based on the sale and purchase of kiosks at Balai Akaik Saruaso, the practice of buying and selling futures kiosks lasts for twenty-five years and PDAM electricity is borne by the kiosk buyer, and the kiosk buyer is required to maintain and maintain the kiosk as well as possible if there is damage during the period of the futures sale and purchase. then the buyer is obliged to repair it with his personal funds, within that period the buyer is unable to continue then the money will not be returned by the Nagari Government, but the solution from the Nagari Government is that the buyer looks for someone else to continue the remaining period, determine the sale and purchase money is deducted with how much time has been used, three months before the end of the sale and purchase period, the kiosk buyer must confirm whether he wants to continue or not, if not, the Nagari Government gives a grace period of one month for the buyer to pack and remove his goods from the inside. stall. Based on muamalah fiqh, the legal status of buying and selling futures kiosks is invalid because in buying and selling there is a transfer of ownership (Al-tiqal al-milkiyyah) i.e. the goods being sold change ownership, from the seller's property to the buyer's property and according to the Syafi'iyah scholars, it is stated that the transfer of ownership of the object exchanged, Al-Muthman) is eternal (eternal) not temporary. while the sale and purchase of the kiosk at Balai Akkaik Saruaso is not permanent, but has a period of 25 years, the contract will end if you want to continue or end the contract, start over again.